Bustān al-Salāṭīn: Representation of Malay Islamic Civilization (Aceh) in the 17th Century - Azizah, Lailiyatul; Hamzah, Norhayati (Journal of Islamic Civilization, 2022)
Bustān al-Salāṭīn is a traditional Islamic text that tells about the history of Malay Islam, especially Aceh. Written in the 17th century by Shaykh al-Islām named Nūr al-Dīn al-Ranīrī (d. 1659), who was then under the rule of Sultan Iskandar Thani (1636-1641). This article discusses how Bustān represents the formation of the Aceh sultanate government system, the sultan who was in power when this manuscript was written, their political behavior, to the evidence of artifacts found based on information in the Bustān manuscript. The manuscript also contains 17th-century intellectual discourse as a marker of the early development of Islam in the Malay world. Reform of Muslim religious practices to change wujūdīyah Sufism. The preparation of Bustān was based on socio-religious conditions in the Aceh sultanate was advancing in the fields of politics and Islamic intellectual development. This article argues Bustān is not only a traditional Malay Islamic ancient text but more than that which can be proven archaeologically whose existence still exists today. Besides that, Bustān contributed to the pilgrimage tradition of the ‘auliyā’ where this practice is common in Java and other parts of the Muslim world. Bustān al-Salāṭīn adalah sebuah naskah tradisional Islam yang bercerita tentang sejarah Islam Melayu khususnya Aceh. Ditulis abad ke-17 oleh Syaikh al-Islām bernama Nūr al-Dīn al-Ranīrī (w. 1659) yang saat itu bawah kekuasaan Sultan Iskandar Thani (1636-1641). Artikel ini membahas bagaimana Bustān merepresentasikan pembentukan sistem pemerintahan kesultanan Aceh yang berkuasa saat naskah ini ditulis, perilaku politik mereka, hingga bukti artefak yang ditemukan berdasar informasi di dalam naskah Bustān. Naskah tersebut juga berisi wacana intelektual abad ke-17 sebagai penanda awal Islam berkembang di dunia Melayu. Reformasi praktik keagamaan umat Islam untuk mengubah sufism wujūdīyah. Penyusunan Bustān didasarkan pada kondisi sosial keagamaan yang pada saat itu kesultanan Aceh maju di bidang politik dan perkembangan intelektual Islam. Artikel ini berargumen bahwa Bustān bukan saja naskah kuno tradisional Islam Melayu, melainkan lebih dari itu yang dapat dibuktikan secara arkeologis yang keberadaannya masih ada sampai sekarang. Disamping itu Bustān berkontribusi pada tradisi ziarah para ‘auliyā’ dimana praktik ini lumrah terjadi di Jawa dan belahan dunia Muslim lainnya.